COASTAL VULNERABILITY INDEX ANALYSIS IN THE ANYER BEACH SERANG DISTRICT, BANTEN - Mawardi Amin; Ika Sari Damayanthi Sebayang; Carolina Masriani Sitompul (Universitas Mercu Buana, 2019)
Anyer Beach is one of the famous tourist destinations. In addition to tourist destinations, the Anyer beach also has residential and industrial areas. In managing coastal areas, a study of vulnerability is needed due to threats from sea level rise, abrasion/erosion and also high waves that can damage infrastructure and cause losses. The research method is to collect data of hydro-oceanography, coastal vulnerability index calculates (Coastal Vulnerability Index). The coastal vulnerability index is a relative ranking method based on the index scale physical parameters such as geomorphology, shoreline change, elevation, sea level rise, mean tidal, wave height. On the results of the analysis of the criteria of vulnerability based on the parameters of geomorphology in the category of vulnerable with scores of 4, shoreline change in the category of vulnerable with a score of 4, the elevation in the category of extremely vulnerable with scores of 5, sea level rise into the medium category with a score of 3, mean tidal in the category less susceptible with a score of 2, the wave height is very vulnerable in the category with a score of 5. The variable that most influences the vulnerability of Anyer Beach is elevation and wave height.